Genotyping for polymorphism of STK-15, a low-penetrance gene in colorectal cancer - Ng, Chen Seng (2008)
STK-15 protein or Aurora-A kinase play a vital role in regulating the cell division process. This preliminary study was conducted to investigate the association of polymorphisms Phe3llle with colorectal cancer development. This nonsynonymous coding region was believed to have important function in regulating the periodically proteasomal-ubiquitination degrading mechanism of STK-15 protein. To examine whether functional variation in STK-15 may affect the susceptible risk, DNA samples from colorectal cancer patients (n = 11) and healthy individual (n = 1) were genotyped for Phe31IIe polymorphisms. Polymerase chain reaction-restriction fragment length polymorphism was used in this study. A restriction enzyme cutting site of Apol is created when there is a polymorphism. Out of 11 samples, 9.09% were Phe/Phe genotype, 72.73% were Phe/Ile genotype and 18.18% were Ile/Ile genotype. The heterozygous might possibly have the highest risk in developing colorectal cancer. The samples were in Hardy-Weinberg-proportion (χ² = 2.393, N=11). Risk of association between polymorphisms of Phe3llle in both alleles and colorectal cancer were investigated using OR, allele Ile was found to have high susceptibility risk (OR=1.20,95% CI = 0.1-22.0) as compared to allele Phe. However, acting as a preliminary study, data obtained indicated that high occurrence rate of Phe3IIle polymorphism can be found in colorectal cancer individuals and it is worth to conduct a large scale and well-designed study in the future.